The effect of applications gibberellic acid and proline on yield of maize (Zea Mays, L.) under water deficit conditions - Al-Shaheen, Mustafa Riyadh Mohammed (School of Bioprocess Engineering, 2016)
Research objectives to investigate the possibility of applying gibberellic acid (GA3) to increase the resistance and productivity of corn to water deficit conditions; to evaluate the capability of applying the proline to reduce the harmful effect of water on the corn; to determine the relationship between a gibberellic acid (GA3) and proline application in water deficit conditions on the corn; to establish the possibility of producing gibberellic acid (GA3) from the regular dry bakery yeast (Saccharomyces cerevisiae) in the laboratory); to assess the crop coefficient (special for Perlis) based on the equation proposed by the FAO and the evaporation basin class (A) and some climate data.